2013
DOI: 10.1093/nar/gkt770
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function analysis of Hmo1 unveils an ancestral organization of HMG-Box factors involved in ribosomal DNA transcription from yeast to human

Abstract: Ribosome biogenesis is a major metabolic effort for growing cells. In Saccharomyces cerevisiae, Hmo1, an abundant high-mobility group box protein (HMGB) binds to the coding region of the RNA polymerase I transcribed ribosomal RNAs genes and the promoters of ∼70% of ribosomal protein genes. In this study, we have demonstrated the functional conservation of eukaryotic HMGB proteins involved in ribosomal DNA (rDNA) transcription. We have shown that when expressed in budding yeast, human UBF1 and a newly identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 53 publications
(96 reference statements)
3
56
1
Order By: Relevance
“…23) By contrast, we confirmed that the box A mutations described here also impaired binding of Hmo1 to the RPS23A promoter (Fig. 4(C)).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…23) By contrast, we confirmed that the box A mutations described here also impaired binding of Hmo1 to the RPS23A promoter (Fig. 4(C)).…”
Section: Discussionsupporting
confidence: 78%
“…21,22) It was reported recently that the integrity of box A is required for the function of Hmo1 in the RNA polymerase I transcription in vivo, whereas the requirement of box A in the transcription of RPG (such as RPS23A) by RNA polymerase II is unclear. 23) In contrast to these previous studies, the box A mutations identified in the genetic screen performed here impaired the ability of Hmo1 to bind to DNA. Furthermore, one of the box A Hmo1 mutants was deficient in DNA binding specifically in vivo.…”
contrasting
confidence: 91%
“…Comparable functions of UBF and HMO1 are supported by the observation that both proteins are highly enriched in the nucleolus and localized throughout the transcribed rDNA region and that both proteins contain HMG domains that may promote DNA bending and DNA looping (149,150,162,163). Further support for overlapping functions of HMO1 and UBF was provided by the observation that the expression of human UBF1 or S. pombe HMO1 also suppresses the rpa49Δ growth phenotype (130).…”
Section: Hmo1 Is a Component Of The Pol I Transcription Machinerymentioning
confidence: 94%
“…HMO1 has also been identified in closely related species such as Saccharomyces kluyveri (129). In addition, an HMO1 counterpart is encoded in the Schizosaccharomyces pombe genome (130). According to the Saccharomyces Genome Database (131), HMO1 has been reported to exhibit physical or genetic interactions with a total of 290 genes or gene products.…”
Section: Yeast Hmgb Protein Hmo1mentioning
confidence: 99%
See 1 more Smart Citation